Implementasi Kebijakan Program Keluarga Harapan (PKH) di Desa Kotayasa, Kecamatan Sumbang, Kabupaten Banyumas - Sutikno, Chamid; Yusuf, Muhammad (Sawala : Jurnal Administrasi Negara, 2023)
The purpose of this research was to describe the implementation process in Kotayasa Village, Sumbang District, Banyumas Regency. This study uses a descriptive method with a qualitative approach, to broadly describe a problem in research conducted based on the answers to the problem. The data collection techniques used in this study are: interviews, observation and documentation. To test the validity of the data, researchers used a source triangulation technique, namely by checking the data that had been obtained through several sources. From the research results it can be seen that the implementation of the Family Hope program is in accordance with existing rules and policies. For the various actors currently involved, starting from PKH assistants at the sub-district level and at the village level, good communication and coordination have been established. The factor that has been a problem in implementing the Family Hope program is to improve the quality of human resources to increase the level of education